Effects of Litsea cubeba Essential Oil Incorporated into Denture Soft Lining Materials - Songsang N. (2023)
The antimicrobial properties, cell cytotoxicity and surface hardness of soft lining materials (GC soft liner, Viscogel and Coe comfort) incorporated with various concentrations of Litsea cubeba essential oil (LCEO) were evaluated. The minimum inhibitory concentrations of LCEO against Candida albicans and Streptococcus mutans were 1.25% v/v and 10% v/v, respectively. However, when LCEO was incorporated into the three soft lining materials (GC soft liner, Viscogel and Coe comfort), 10% v/v and 30% v/v of LCEO could inhibit the growth of C. albicans and S. mutans, respectively. The extracts of soft lining materials with 10% and 30% v/v LCEO, 2% chlorhexidine, 30% v/v nystatin and no additive were used for cytotoxicity tests on a human gingival fibroblast cell line. There was no significant difference in cell viability in all groups with additives compared to the no additive group (p > 0.05). Surface hardness increased significantly between 2 h and 7 day incubation times in all groups, including the controls (p < 0.05). A higher LCEO concentration had a dose-dependent effect on the surface hardness of all soft lining materials (p < 0.05). However, the surface hardness of materials with additive remained in accordance with ISO 10139-1. LCEO could be used as a natural product against oral pathogens, without having a negative impact on soft lining materials.